2019
DOI: 10.1029/2019gl082412
|View full text |Cite
|
Sign up to set email alerts
|

Traveling Ionospheric Disturbances at Mars

Abstract: We report the first extraterrestrial observation of traveling ionospheric disturbances (TIDs) in the ionosphere of Mars (below ≈160 km) by NASA's Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft. TIDs are ionospheric waves manifesting as an oscillation in density, velocity, and composition of ionospheric plasma. The TIDs were encountered in the Martian dynamo region, where ions are collisionally bound to the neutral thermosphere but electrons remain frozen in to the local magnetic field. The underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…For example, MEX/MARSIS in the Active Ionospheric Sounding (AIS) mode, one of the two main data providers for previous statistical studies on ionospheric disturbances, has limited coverage of the Martian nightside ionosphere, as shown by Harada et al (2018, Figure 3d) and pointed out therein. While MAVEN is largely free from this LT coverage limit, some of the previous climatological studies focused only on altitudes below 200 km (e.g., Collinson et al, 2019;Fowler et al, 2019;Tian et al, 2022). Thus far, published ionospheric disturbance reports using MAVEN data did not cover more than 6.5 years (e.g., Andrews et al, 2023;Basuvaraj et al, 2022;Tian et al, 2022).…”
Section: Room For Improvement Over Existing Studies On Martian Ionosp...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MEX/MARSIS in the Active Ionospheric Sounding (AIS) mode, one of the two main data providers for previous statistical studies on ionospheric disturbances, has limited coverage of the Martian nightside ionosphere, as shown by Harada et al (2018, Figure 3d) and pointed out therein. While MAVEN is largely free from this LT coverage limit, some of the previous climatological studies focused only on altitudes below 200 km (e.g., Collinson et al, 2019;Fowler et al, 2019;Tian et al, 2022). Thus far, published ionospheric disturbance reports using MAVEN data did not cover more than 6.5 years (e.g., Andrews et al, 2023;Basuvaraj et al, 2022;Tian et al, 2022).…”
Section: Room For Improvement Over Existing Studies On Martian Ionosp...mentioning
confidence: 99%
“…(2018, Figure 3d) and pointed out therein. While MAVEN is largely free from this LT coverage limit, some of the previous climatological studies focused only on altitudes below 200 km (e.g., Collinson et al., 2019; Fowler et al., 2019; Tian et al., 2022). Thus far, published ionospheric disturbance reports using MAVEN data did not cover more than 6.5 years (e.g., Andrews et al., 2023; Basuvaraj et al., 2022; Tian et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The latter are largely created by GWs propagating from below and, thus, couple vertical atmospheric layers. Recently, the first observation of the extraterrestrial TIDs of the second kind has been reported in the ionosphere of Mars [137].…”
Section: Ionospheric Effectsmentioning
confidence: 99%
“…All these processes are entangled between several regions of the system. Understanding their temporal and spatial variability in order to assess the differences of the processes that control the long-term dynamics of an ionosphere, including the role of the electrodynamics induced by the solar wind at Mars along the solar cycle and the motion and dynamics of the neutral atmosphere, which in turn can also create currents in the ionosphere (Riousset et al, 2014;Collinson et al, 2019), is a critical aspect for exploration of the red planet that we must resolve (Lillis et al, 2021;Sanchez-Cano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%